Menyulut Aksara Gunungpati : Memadukan Literasi dan Inklusi Sosial - Heru Eko Prasetyo; Wawan Wibisono; Puji Setya Sunarka (Jurnal Pengabdian Masyarakat Waradin, 2025)
Low interest in reading and limited access to digital literacy in Gunungpati Village, Semarang, are the main challenges in developing community literacy, especially among children and teenagers. The community service program "Gunungpati Reading Literacy Movement" aims to increase interest in reading and digital literacy by providing physical reading corners, digital libraries, and literacy training. The methods used include literacy outreach, training in reading, writing and digital literacy, and the application of technology through digital libraries that the public can access at any time. This program involves collaboration with various parties, such as sub-district government, PKK, educational institutions and local communities.The results of this program show an increase in reading interest by being available in reading corners and digital libraries that are accessed by the public. With this program, it is hoped that the Gunungpati community will increase their literacy and technology skills, so that they can support increased social and economic welfare. The program is also designed to be sustainable through strong partnerships and ongoing support.